Building bridges between halide perovskite nanocrystals and thin-film solar cells. Issue 11 (26th September 2018) - Yang, Hanjun; Zhang, Yi; Hills-Kimball, Katie; Zhou, Yuanyuan; Chen, Ou
Abstract : Perspectives on how halide perovskite nanocrystals are better integrated in perovskite solar cells are provided. Abstract : The development of halide perovskite (HP) based thin film solar cells has been unprecedented in the past few years, and there is significant ongoing effort aiming to make perovskite solar cells (PSCs) more efficient and stable. Parallel to the PSC research, there is growing interest in exploring the synthesis and physiochemical behaviors of HP nanocrystals (NCs). While these HP NCs inherently possess many unique properties that are suitable for the use in PSCs, the reported effort of incorporating HP NCs into PSCs is still highly limited. As a result, there is a gap between HP NC and PSC research. In this context, we provide here a brief review of the established HP NC synthesis and a discussion of the several recent studies pertaining to the use of HP NCs in PSCs. Based on these, we provide perspectives on promising directions for bridging the gap between HP NC and PSC research in the future.